DESIMINASI PEMANFAATAN DAUN SEREH WANGI UNTUK SABUN CAIR RAMAH LINGKUNGAN PADA SISWA SD - Heri Satria; Mulyono; Suripto Dwi Yuwono; Ridho Sholehurrohman; Kamisah D. Pandiangan; Diky Hidayat (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
Education based on environmental awareness plays an essential role in shaping a generation that cares about the environment and sustainability. One effective approach to raising this awareness is by integrating simple science that focuses on the use of natural materials in everyday life. Lemongrass (Cymbopogon citratus), which is rich in bioactive compounds like citronella and geraniol, offers various benefits, including antibacterial and anti-inflammatory properties. This program aims to educate students, teachers, and parents on how to process lemongrass into eco-friendly liquid soap, as well as teach practical skills that can be applied in daily life. Through this training, students will not only understand the benefits of natural materials but also acquire skills that can be used to create economic opportunities based on environmentally friendly products. This program also encourages a healthy and sustainable lifestyle by reducing dependence on harmful chemical-based commercial cleaning products. Furthermore, the program aims to introduce the concept of entrepreneurship based on natural products, which can create new economic opportunities at the local level. The implementation of this community service program will involve students, teachers, and parents at SD Negeri 2 Pampangan, Sekincau District, West Lampung. Through hands-on training, it is expected to have a significant positive impact on improving the competence of students, teachers, and parents in effectively utilizing natural resources. Additionally, this program has the potential to serve as a model that can be implemented in other schools across Indonesia, expanding its positive impact and raising environmental awareness among the younger generation.